Aplicação do ultrasson terapêutico no tratamento da lipodistrofia ginóide - Siqueira, Karina da Silva (2014)
The objective of this study was to analyze the effects of a treatment protocol with high power therapeutic ultrasound on the gynoid lipodystrophy (GLD). The analysis was done using the Ulrich's scale, photographic records, perimetry, bioimpedance and through the application of a specific GLD satisfaction questionnaire to the research volunteers. The study included 20 female volunteers who were submitted to anamnesis, physical examination, perimetry, bioimpedance, photographic records and answered the specific GLD satisfaction questionnaire, before and after the treatment. Twelve applications of ultrasound Avatar Cuatro ® 3 MHz with neutral gel were carried out in continuous mode, with an intensity of 2.8 W/cm² and 42 W of power. The tests were accomplished in the frequency of 3 times a week, totaling 4 weeks for each volunteer. The comparison between the variables analyzed pre and post intervention was performed by ANOVA and Student's t-test. The differences were considered statistically significant at p ≤ 0.05. The mean age of the volunteers group was 34 ± 10 years. There was no statistically significant variation in the variables of weight (p = 0.764), fat percentage (p = 0.864), percentage of liquid (p = 0.883), the body mass index (BMI) (p = 0.718), the perimetry (p > 0.05). However, there was statistically significant variation in the degree of GLD measured by Ulrich's scale (p = 0.007) and in the satisfaction questionnaire results pre and post-intervention (p = 0.003). It was not possible to conclude, statistically, that the ultrasound is effective in reducing localized fat, even with a decrease in the perimetry of most of the volunteers. However, it was possible to conclude that the physiotherapy treatment protocol proposed in this work was effective in promoting the improvement of the appearance of GLD.